PENYEDIAAN HUNIAN YANG LAYAK BAGI LANSIA SEBAGAI PELAYANAN MENGHADAPI AGEING POPULATION DI JAKARTA - Hansen Leonardo; Sidhi Wiguna Teh (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Population growth in Indonesia is a concern to prevent population growth. The elderly community is targeted because the number of elderly people can bring Indonesia into the era of the Ageing Population. This study discusses solutions to deal with the increasing elderly population in the next few years by providing decent housing and improving the quality of life of the elderly. By using a qualitative method which is realized in the form of a design, it is hoped that it can be a solution to the existing problems. Of course, by not forgetting several factors that must be considered in maintaining and improving the quality of life of the elderly. Keywords: Elderly Population; population density; elderly; population growth; housing provision Abstrak Pertumbuhan penduduk di Indonesia menjadi perhatian untuk mencegah terjadinya lonjakan jumlah penduduk. Masyarakat lansia menjadi sasaran dikarenakan jumlah masyarakat lansia dapat membawa negara Indonesia memasuki era Ageing Population. Dalam penelitian ini membahas solusi untuk menghadapi pertambahan penduduk lansia dalam beberapa tahun kedepan dengan memberikan hunian yang layak serta meningkatkan kualitas hidup lansia. Dengan menggunakan metode kualitatif yang diwujudkan dalam bentuk desain diharapkan dapat menjadi solusi dari permasalahan yang ada. Tentu saja dengan tidak melupakan beberapa faktor yang harus diperhatikan dalam menjaga dan meningkatkan kualitas hidup para masyarakat lansia.